Tugas dan Kewajiban Peserta Didik dalam Perspektif Filsafat Pendidikan Islam: Analisis Kontekstual dan Praktis dalam Pembelajaran - Zahra, Amatullah Taqiya; Anwar, Saiful (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2024)
This study aims to explore the duties and responsibilities of learners in the context of Islamic education, as well as to analyse the influence of spiritual reflection and learning atmosphere on learners' motivation to learn at MSU Nashrus Sunnah. This research employed a qualitative approach, utilizing a case study method. Data was collected through interviews with teachers and learners, direct observation of learning activities, and analysis of documentation related to the implementation of spiritual reflection and the learning atmosphere in the classroom. The results show that regular spiritual reflection at MSU Nashrus Sunnah can improve learners' motivation to learn in the short term. However, the effectiveness of this method in the long term needs further investigation. In addition, a conducive learning atmosphere, such as physical activities and attention to learners' physical and mental well-being, was found to increase their engagement and motivation. Learners' characteristics, including interests and learning styles, also influence how teachers adjust teaching methods. This study provides important implications for teachers to pay attention to the individual characteristics of learners and create a pleasant learning atmosphere. Further research is needed to evaluate the long-term impact of spiritual reflection on learning motivation. In addition, collaboration with parents to support learners' physical and mental well-being is required in order to create a more effective learning process.